Enhanced optical absorption and photocatalytic water splitting of g-C3N4/TiO2 heterostructure through C&B codoping: A hybrid DFT study. (24th February 2021) - Lin, Yanming; Wang, Qi; Ma, Mintong; Li, Peiying; Maheskumar, V.; Jiang, Zhenyi; Zhang, Ruiqin
Abstract: Our theoretical research indicate that the electric field are generated in the direction of (C doped) TiO2 (101) surface to (B-doped) g-C3 N4 monolayer for the pristine, C and B doped g-C3 N4 /TiO2, and higher band-edge potential on the (C doped) TiO2 (101) surface are observed compared to (B-doped) g-C3 N4 monolayer. Thus, the pristine (2.591 eV), C-doped (2.663 eV) and B-doped (2.339 eV) g-C3 N4 /TiO2 are Z-scheme heterostructures, which promotes charge separation and retains a prominent redox ability. After C doping, the C 2 p energy level is introduced which facilitate the separation of photoexcited carriers. The B-doped g-C3 N4 /TiO2 has a reduced bandgap and the mixing of B 2 p and N 2 p energy levels, promoting the red-shift of the optical absorption edge. The C&B codoped g-C3 N4 /TiO2 follows type-II charge transfer mode because of their synergistic effect in C and B atoms, which changes the direction of the built-in electric field. It also has a narrow bandgap (1.309 eV) and effectively separate electron-hole pairs leading to strong optical absorption ability in the range of 360 nm–460 nm. The band-edges matching of the semiconductor photocatalyst and the direction of the built-in electric field jointly determine whether the charges are selected to be Z-scheme or II-type transfer mode. Based on g-C3 N4 /TiO2 for C or/and B (co)doping, their different charge transfer modes have been established and they are expected to show promising photocatalytic water splitting performance. Graphical abstract: Image 1 Highlights: Z-scheme pure, C and B single-doped g-C3 N4 /TiO2 have prominent redox ability. Type-II C&B codoped g-C3 N4 /TiO2 improves the separation of electron-hole pairs. C or/and B (co)doping introduce impurity energy levels to narrow the bandgap of g-C3 N4 /TiO2 . Both Z-scheme and type-II charge transfer modes enhance the optical absorption capacity.